From lipid second messengers to molecular motors: microtubule‐organizing center reorientation in T cells. Issue 1 (10th October 2013) - Huse, Morgan; Le Floc'h, Audrey; Liu, Xin
Summary: In T lymphocytes, polarization of the microtubule‐organizing center (MTOC) to the immunological synapse enables the directional secretion of cytokines, cytolytic factors, and other soluble molecules toward the antigen‐presenting cell. This is likely to be crucial for maintaining the specificity of T‐cell effector responses. Here, we review recent advances in our understanding of MTOC reorientation in T cells, focusing first on the importance of diacylglycerol and protein kinase C isozymes and then on the molecular motor proteins that function downstream to drive MTOC movement.